Expressive illocutionary act found in the “after” movie - Padmi, Ni Luh Indriyani; Suastini, Ni Wayan; Pratiwi, Desak Putu Eka (Journal of Language and Applied Linguistics, 2022)
According to Yule (1996: 47), expressives are utterances by speakers that express their mental state, they categorize psychological states and can be in the form of statements of pleasure, pain, dislike, joy and sorrow. This study concerns the expressive illocutionary act used in the After movie. The aim of this study is to analyze the types of expressive illocutionary acts and the context of the situation. This study used a qualitative method to analyze the data and documentation method used in collecting the data found in the movie. The data were taken from the After movie. Based on Searle (1967) and Yule (1962) theory about the types of expressive illocutionary act and supported by theory context of the situation by Halliday and Hasan (1985).